An investigation of multiplier effects generated by implementing queue jump lanes at multiple intersections. Issue 8 (27th October 2016) - Truong, Long T.; Sarvi, Majid; Currie, Graham
Summary: This paper investigates the combination effects of queue jump lanes (QJLs) on signalised arterials to establish if a multiplier effect exists, that is, the benefit from providing QJLs at multiple intersections is higher than the sum of benefits from providing them individually at each of those intersections. To explore the combination effects on bus delay and total person delay, a delay estimation model is developed using kinematic wave theory, kinematic equations and Monte Carlo simulation. In addition, to investigate the combination effects in offset settings optimised for bus delay or total person delay, offset optimisation models are proposed. Validation results using traffic micro‐simulation indicate the effectiveness and computational efficiency of the proposed models. Results of a modelling test bed suggest that providing QJLs at multiple intersections can create a multiplier effect on one‐directional bus delay savings with signal offsets that provide bus progression. Furthermore, optimising offsets to minimise bus delay tends to create a multiplier effect on one‐directional bus delay savings, particularly when variations in dwell times are not high. The reason for the multiplier effect may be that providing QJLs reduces variations in bus travel times, which makes signal coordination for buses perform more effectively. From a policy perspective, the existence of a multiplier effect suggests that a corridor‐wide scale implementation of QJLs has considerable merit. Copyright © 2016 John Wiley & Sons, Ltd.